Measuring Marketing Performance, Practices and Management Control Challenges - Thaker, Keyur (Indian Journal of Marketing, 2010)
Marketers are happy speaking their own language, replete with jargon like "awareness," "share of requirements" and "customer satisfaction." Such terminology works fine in the marketing department and with the advertising professionals, who execute marketing plans. However, there's a translation problem between that language and the language of profitability and stock price, which is the mother tongue of corporate chief executives (CEOs) and Chief Financial officers (CFO's). "CEOs want to know what a 5% increase in customer satisfaction will do for the bottom-line," But in general, the marketing discipline has always been more art than science. Corporates spend untold billions of cash on marketing without any exacting way of determining how much the resulting "brand equity" or "consumer awareness" contributes to the bottom line. However, the question is not whether such expenses in marketing contribute to the bottom line but how much.